Flux growth at 1230 °C of cubic Tb2O3 single crystals and characterization of their optical and magnetic properties. Issue 3 (30th October 2014) - Veber, Philippe; Velázquez, Matias; Gadret, Grégory; Rytz, Daniel; Peltz, Mark; Decourt, Rodolphe
Abstract : The crystal growth of cubic Tb2 O3 was achieved for the first time and its high Verdet constant was determined. Abstract : In this work, we present the first crystal growth of cubic Tb2 O3 single crystals by a controlled atmosphere flux method which uses a heavy metal free solvent working at less than half the melting temperature of this sesquioxide. Cubic millimeter-sized crystals extracted from as-grown boules are phase (powder XRD) and chemically (GDMS) pure and exhibit a Verdet constant in the visible and near-infrared spectral ranges, which is at least three times higher than that of a commercial Tb3 Ga5 O12 (TGG) crystal. The 1.36 mm thick crystals display a transmission coefficient higher than 77% over the 525 nm–1.38 μm spectral range. The absorption spectrum, magnetic susceptibility and specific heat measurements on the single crystals confirm the absence of detectable Tb 4+ cations and other impurities.